2020
DOI: 10.1186/s12902-020-00565-w
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, an independent predictor for survival of gastric neuroendocrine neoplasm patients: a SEER database analysis

Abstract: Background: Marital status proves to be an independent prognostic factor in a variety of cancers. However, its prognostic impact on gastric neuroendocrine neoplasms (G-NEN) has not been investigated. Methods: We identified 3947 G-NEN patients from the Surveillance, Epidemiology, and End Results (SEER) database. Meanwhile, propensity scores for marital status were used to match 506 unmarried patients with 506 married patients. We used Kaplan-Meier method and multivariate Cox regression to analyse the associatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This could be explained by the fact that socioeconomic psychological factors and genetic diversity might play an important role in tumorigenesis and tumor progression [18,19]. Several previous studies demonstrate that marital status and ethnicities were important etiological and prognostic factors in several solid tumors, including cervical cancer [20][21][22][23]. Similarly, in our study, better survival was seen in married patients and in white women.…”
Section: Discussionsupporting
confidence: 77%
“…This could be explained by the fact that socioeconomic psychological factors and genetic diversity might play an important role in tumorigenesis and tumor progression [18,19]. Several previous studies demonstrate that marital status and ethnicities were important etiological and prognostic factors in several solid tumors, including cervical cancer [20][21][22][23]. Similarly, in our study, better survival was seen in married patients and in white women.…”
Section: Discussionsupporting
confidence: 77%
“…It was notable that marital status was also an independent meaningful factor in the present study. Marital status has been reported as an independent prognostic factor on the prognosis of many malignancies, and marriage appeared to have a protective effect in these studies, with married patients having better 5-year OS and CSS outcomes than unmarried patients, including divorced/separated, widowed, and single patients (31)(32)(33). Compared with unmarried individuals, married individuals generally have more advantageous financial situations and emotional support from their husbands or wives, thus they will adhere better to treatment and have better outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…However, due to a lack of demographic information, the AJCC system is not a perfect predictor of CSS in EC patients. Previous studies have confirmed that age at diagnosis, gender, race, marital status, and occupation are significantly associated with cancer survival (8)(9)(10). In the establishment of prognostic models for patients with EC, the prognostic value is limited due to the relatively limited sample size (11,12).…”
Section: Discussionmentioning
confidence: 99%